Biologically Enhanced Genome-Wide Association Study Provides Further Evidence for Candidate Loci and Discovers Novel Loci That Influence Risk of Anterior Cruciate Ligament Rupture in a Dog Model - Baker, Lauren A.; Momen, Mehdi; McNally, Rachel; Berres, Mark E.; Binversie, Emily E.; Sample, Susannah J.; Muir, Peter (Frontiers in Genetics, 2021)
Anterior cruciate ligament (ACL) rupture is a common condition that disproportionately affects young people, 50% of whom will develop knee osteoarthritis (OA) within 10 years of rupture. ACL rupture exhibits both hereditary and environmental risk factors but the genetic basis of the disease remains unexplained. Spontaneous ACL rupture in the dog has a similar disease presentation and progression, making it a valuable genomic model for ACL rupture. Variable breed predisposition supports a genetic influence and extensive linkage disequilibrium facilitates genome-wide association study (GWAS). We leveraged the dog model with Bayesian mixture model (BMM) analysis to identify novel and relevant genetic variants associated with ACL rupture. Differential gene expression analysis using RNA-Seq was performed on case and control ACL and synovial tissues. Biological priors were incorporated into GWAS analysis by assigning SNPs within differentially expressed genes to separate mixture classes using BayesRC. SNPs were also assigned to a separate class if they occurred within candidate genes identified previously in published literature. The SNPs exhibiting the largest effects were found within or near genes associated with regulation of the actin cytoskeleton and the extracellular matrix. Two of the largest associations are located near regions under selection in the Labrador Retriever population. The results of the current analysis are consistent with previous work published by our laboratory and others, and also highlight new genes in biological pathways that have not previously been associated with ACL rupture. These results provide further support for the hypothesis that extracellular matrix proteins play a role in predisposition to ACL rupture. The genetic associations identified in this study mirror those found in human beings, which lays the groundwork for development of disease-modifying therapies for both species.